Conducting ethical internet-based research with vulnerable populations: A qualitative study of bereaved participants’ experiences of online questionnaires - Smith, KV; Thew, G; Graham, B (Taylor and Francis, 2018)
Background: Bereavement can be considered a potentially traumatic experience, and concerns have been raised about conducting grief research responsibly online. Objective: Given that online research introduces new methodological opportunities and challenges, we aimed to develop a greater understanding of how bereaved individuals experience online research participation. Method: One day after participation in an online grief study, 876 participants, bereaved on average 40 months, received a ‘check-in’ email to support wellbeing and offer further contact if needed. Although not explicitly asked to respond if no help was needed, 300 participants sent email replies, with only six requesting support. These responses were analysed qualitatively using Content Analysis. Results: Results suggested participants found it acceptable to be asked about their grief and while difficult emotions were frequently described in response to the questionnaires, these reactions were temporary. A range of positive reactions were also reported, including new realizations arising from completing the research and changes in thinking related to grief. Participants also wrote about their appreciation for the study and how it was carried out, as well as a desire to contribute more to the study and to help others in a similar position. Conclusions: We suggest that the use of the check-in email to support wellbeing following study completion, along with advice on preparing to take part, contributed to positive experiences of participation and we recommend these strategies for future studies. These findings could allay clinical concerns about conducting online research with vulnerable populations, as well as raising questions about the possible therapeutic impact of measurement.